The role of hypoxia-inducible factors in metabolic diseases - Gonzalez, Frank J. (Nat Rev Endocrinol, 2018)
Hypoxia-inducible factors (HIFs), a family of transcription factors activated by hypoxia, consist of three α-subunits (HIF1α, HIF2α and HIF3α) and one β-subunit (HIF1β), which serves as a heterodimerization partner of the HIFα subunits. HIFα subunits are stabilized from constitutive degradation by hypoxia largely through lowering the activity of the oxygen-dependent prolyl hydroxylases that hydroxylate HIFα, leading to their proteolysis. HIF1α and HIF2α are expressed in different tissues and regulate target genes involved in angiogenesis, cell proliferation and inflammation, and their expression is associated with different disease states. HIFs have been widely studied because of their involvement in cancer, and HIF2α-specific inhibitors are being investigated in clinical trials for the treatment of kidney cancer. Although cancer has been the major focus of research on HIF, evidence has emerged that this pathway has a major role in the control of metabolism and influences metabolic diseases such as obesity, type 2 diabetes mellitus and non-alcoholic fatty liver disease. Notably increased HIF1α and HIF2α signalling in adipose tissue and small intestine, respectively, promotes metabolic diseases in diet-induced disease models. Inhibition of HIF1α and HIF2α decreases the adverse diet-induced metabolic phenotypes, suggesting that they could be drug targets for the treatment of metabolic diseases.